2012
DOI: 10.1093/cid/cis840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Type of Diagnostic Assay on Clostridium difficile Infection and Complication Rates in a Mandatory Reporting Program

Abstract: Performing PCR instead of EIA/CCA is associated with a >50% increase in the CDI incidence rate. Standardization of diagnostic methods may be indicated to improve interhospital comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
166
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 35 publications
9
166
1
5
Order By: Relevance
“…20 The diagnostic method used in our study (QUIK CHEK COMPLETE, Techlab, US) was chosen as toxin detection in faecal samples correlates with clinical outcome, whilst detection of a toxigenic strain does not. 12,13 Toxin detection is therefore a better indicator of clinically relevant CDI. Our false-negative rate was much lower (1.6% vs. 19.0%) compared with a previous study, but this used toxigenic culture to determine CDI status, which will over-estimate clinically relevant CDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The diagnostic method used in our study (QUIK CHEK COMPLETE, Techlab, US) was chosen as toxin detection in faecal samples correlates with clinical outcome, whilst detection of a toxigenic strain does not. 12,13 Toxin detection is therefore a better indicator of clinically relevant CDI. Our false-negative rate was much lower (1.6% vs. 19.0%) compared with a previous study, but this used toxigenic culture to determine CDI status, which will over-estimate clinically relevant CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, detection of C. difficile toxin in patient faecal samples, as opposed to toxigenic C. difficile (strains that produce toxin in vitro, or have toxin genes present), correlates with disease severity and mortality. 12,13 To improve the sub-optimal sensitivity of commercially available toxin detection assays, two-stage laboratory diagnosis, involving a sensitive C. difficile screening test followed by a C. difficile toxin assay is recommended. 1,12 Nevertheless, a questionnaire-based study in 125 European laboratories in 2010 showed wide variation in use of CDI diagnostic methods, with a quarter still using a single assay.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Adult and pediatric centers that implemented PCR-based assays for the detection of C. difficile in replacement of EIA noticed an increase in the proportion of positive C. difficile tests by 2-to 10-fold. [22][23][24] For instance, Luna et al 22 reported an increase in the proportion of C. difficile positivity from an average of 8% to 16.2% after switching from EIA to PCR. We similarly show that switching from ELISA to PCR increased the number of identified cases by more than 2-fold.…”
Section: Discussionmentioning
confidence: 99%
“…25 This is supported by the fact that in adult populations, the complication rate in patients with CDI is 40%-50% higher if they were diagnosed with EIA or cytotoxicity assay compared with PCR. 23,25 In pediatrics, the complication rates are significantly lower compared with adults. 16 Toxigenic C. difficile carriage has been documented in healthy adults with a rate that was reported to be as high as 14% in hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Bauer et al 3 sensitive polymerase chain reaction-based tests may result in a substantial reporting of low-severity CDI cases and C. difficile carriers who develop diarrhea for another reason. 7 Until we take measures to quantify and understand the relationship between the reported incidence, frequency and mode of testing, and frequency of complicated C. difficile infections, reported CDI rates could depend on how hard hospitals look for what they do not want to find.…”
mentioning
confidence: 99%